Counter-claiming and indicating gaps in English RAIs in the Indonesian context - Warsidi, Warsidi (JOALL (Journal of Applied Linguistics and Literature), 2026)
Genre of research article introductions (RAIs) have received increasing numbers of scholarly research worldwide, including in the Indonesian context, and establishing a niche has been previously addressed in the literature. However, studies to justify current research in Indonesian contexts are still limited, particularly those published in accredited Sinta journals, while understanding how to establish a niche is pivotal to provide understanding and awareness to students and novice authors. This study aims to address this need by analyzing counter-claiming and indicating a gap to establish a niche in 100 English RAIs written by Indonesian authors in the discipline of language education published in Sinta 2-accredited journals, and how authors linguistically realize these two communicative steps. It used genre-based analysis, more specifically, the Move 2 Establishing a niche of create research space (CARS) model as an analytical framework. The results revealed that an evolving genre has occurred in this study. Indonesian authors employed counter-claiming and indicated a gap for establishing a niche. However, while counter-claiming is optional, indicating a gap is conventional in this study. To realize these two steps, the authors employed linguistic strategies to justify their current research areas. These results imply that genre in English RAIs in the present study may become future examples and as a starting point for evolving genre. The reason behind these findings are discussed further in the discussion section.